Analysis of strategic planning and its influence on political-electoral results from the study of the first round of the Chilean presidential campaign of 2017 - Francisco Grandón González (2020)
The study and implementation of the electoral campaigns in Chile and latin america is giving its first steps, so that the development of profesionals in the área and the analysis of the planification processlacks of the relevance that should have. In this paper it will report the results of a qualitative research, that analyzed the relevance that have the different stages of the strategic process of planning an electoral campaign and its impact in the final results of the first round of the 2017 chilean presidential campaign, specifically the cases of the candidates Marco Enríquez-Ominami, Alejandro Guillier, Alejandro Navarro y Beatriz Sánchez. It was consulted through semi-structured interviews to the presidentials candidates, advisors and campaign managers, it were defined some key themes related to the planification procces of each campaign asociated to a candidacy. Thus, the analysis and tabulation process give us a interest comparative between the answers of the candidates and advisors, that confronted with theoretical contextualization, allow us to develop a battery of suggestions to revalue the profesional communicator figure and its role as advisor to obtain better political-electoral outcomes.